2013
DOI: 10.1007/s11999-013-3138-9
|View full text |Cite
|
Sign up to set email alerts
|

Do Psychiatric Comorbidities Influence Inpatient Death, Adverse Events, and Discharge After Lower Extremity Fractures?

Abstract: Background Psychiatric comorbidity is known to contribute to illness (the state of feeling unwell/unable to rely on one's body) and increased use of healthcare resources, but the effect on inpatient outcomes in fracture care is relatively unexplored. Questions/purposes Our primary null hypothesis is that a concomitant diagnosis of depression, anxiety, dementia, or schizophrenia is not associated with (1) discharge to another care facility rather than home after lower extremity fractures. Secondary study questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 40 publications
2
39
1
Order By: Relevance
“…A diagnosis of dementia appears to condemn hospitalized patients to be discharged to another medical facility rather than home [33,34]. In a previous large cross-sectional survey in Japan, patients with dementia were more likely to be discharged from an intermediate care facility to places other than home [35].…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of dementia appears to condemn hospitalized patients to be discharged to another medical facility rather than home [33,34]. In a previous large cross-sectional survey in Japan, patients with dementia were more likely to be discharged from an intermediate care facility to places other than home [35].…”
Section: Discussionmentioning
confidence: 99%
“…First, the NHDS dataset is based on billing data from ICD-9-CM codes, and such a coding system may not fully capture the patient population of interest [1]. In particular, it has been suggested that administrative databases tend to underreport chronic medical conditions that are considered less acute in the perioperative orthopaedic surgery setting [16,31,33,34,39]. Second, the possibility of errors in coding of the diagnoses and procedures cannot be avoided [7]; however, misclassification mistakes distribute evenly in large-scale studies [53].…”
Section: Discussionmentioning
confidence: 99%
“…Patient demographic information, hospital characteristics, and inpatient outcomes such as discharge disposition and hospital length of stay also were collected. Recognizing its utility to answer valuable clinical questions, the NHDS has been used extensively to analyze data associated with a wide range of diagnoses and procedures across different medical specialties [3,25,33,34,38,44,48]. Because of prior adequate data deidentification, our study was exempt from institutional review board approval.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations